Artikel Kesejahteraan Masyarakat di Desa Campakasari Kecamatan Cempaka Purwakarta: Kesejahteraan - Wawan Oktriawan; Adriansah Adriansah; Siti Alisa (Muttaqien, 2022)
The purpose of this study was to determine the level of community welfare in Campakasari village, Campaka district, Purwakarta district. The research was conducted in Campakasari village, Campaka sub-district, Purwakarta district. The population in this study was the entire community in Campakasari village, Campaka district, Purwakarta district, amounting to 2,285 families. The sample in this study was 90 heads of families. The data collection technique used is interview. The data analysis technique used is descriptive qualitative analysis. The results showed that the level of community welfare was 26 respondents (29%) belonging to the prosperous family I, 51 respondents (57%) belonging to the prosperous II, and 13 respondents (14%) belonging to the prosperous III. All of the people studied were categorized as moderate or not poor because their income reached the minimum wage, the prosperous family I was IDR 3,500,000, meanwhile the prosperous society II was IDR 4,000,000 and the prosperous community group III was IDR 4,500,000.